Covid-19 Self Reporting Information System in Educational Environment Based Website - Bobi Kurniawan; Sopian Alviana (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
This research aims at facilitating the recording of employees and lecturers in the UNIKOM campus environment, who are infected with Covid-19. Using the UNIKOM Covid-19 Task Force Information System, recording and reporting will be more efficient and safer, and there is a more accurate tracing process compared to manual recording. In this research, the development of the system used the system development life cycle (SDLC) waterfall method and descriptive analysis. The results of this study are in the form of websites that can help the data input process or self-reporting of employees and lecturers infected with COVID-19 especially in the UNIKOM environment only.